Lectures on algebraic topology - Miller, Haynes (Singapur: World Scientific Publishing Co. Pte. Ltd., 2023)
Algebraic Topology and basic homotopy theory form a fundamental building block for much of modern mathematics. These lecture notes represent a culmination of many years of leading a two-semester course in this subject at MIT. The style is engaging and student-friendly, but precise. Every lecture is accompanied by exercises. It begins slowly in order to gather up students with a variety of backgrounds, but gains pace as the course progresses, and by the end the student has a command of all the basic techniques of classical homotopy theory.
Singular homology -- Computational methods -- Cohomology and duality -- Basic homotopy theory -- The homotopy theory of CW complexes -- Vector bundles and principal bundles -- Spectral sequences and Serre classes -- Characteristic classes Steenrod operations and cobordism
Includes bibliography and index